Feasibility Analysis Of Implementation In Palm Oil Processing Factories Using The House Of Method Risk - Jundullah, Muhammad; Gani, Mardhiah; Ahistasari, Asih; Hahury, Sanny; Akram, Darul (PT. SAFARI AMALIA, 2024)
This study assesses the effectiveness of the House of Risk (HOR) method in mitigating supply chain risks within palm oil processing plants. By integrating Failure Mode and Effects Analysis (FMEA) with House of Quality (HOQ), the method identifies and prioritizes risk factors while proposing actionable measures for risk mitigation. Findings demonstrate that adopting the HOR method contributes to decreased liquid waste generation and enhanced production efficiency. Additionally, a bibliometric analysis of scholarly publications reveals a notable growth in research focused on risk management in the palm oil sector between 2014 and 2024. This highlights a growing recognition of the importance of systematic risk assessment and management strategies in enhancing sustainability and operational resilience within palm oil processing. The study underscores the HOR method's utility as a comprehensive approach to addressing complex supply chain challenges, thereby promoting sustainable practices and operational excellence in the industry.